Solvent-Free Biginelli Condensation using Tungstate Sulfuric Acid: a Powerful and Reusable Catalyst for Selective Synthesis - Rezvan Rezaee Nasab; Bahador Karami; Saeed Khodabakhshi (Bulletin of Chemical Reaction Engineering & Catalysis, 2014)
Tungstate sulfuric acid (TSA) has been prepared and used as a recyclable catalyst for the Biginelli syn-thesis of some biologically active quinazolinones/thiones under solvent-free conditions. This method has advantages such as the avoidance of organic solvents, high yield of pure products, short reaction times, and operational simplicity. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)